2020
DOI: 10.1017/ice.2019.371
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of economic evaluation in fecal microbiota transplantation

Abstract: Background:Fecal microbiota transplantation (FMT) is an effective therapy in recurrent Clostridium difficile infection (rCDI). It is only recommended for this indication by European and American guidelines. Other indications of FMT are being studied, such as inflammatory bowel disease (IBD), and they have shown promising results.Objectives:To identify and review published FMT-related economic evaluations (EEs) to assess their quality and the economic impact of FMT in the treatment of these diseases.Data source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…The cost-effective analysis from the payer's perspective is crucial for health authorities to create a reimbursement policy for FMT in rCDI. Despite the limited number of cases, variations in antibiotic and FMT costs, and the heterogeneous study designs of published FMT-related economic evaluation studies across different countries, the latest systematic review published in 2020 concludes that FMT appears to be a cost-effective treatment for rCDI ( 31 ). However, only one study from Hong Kong based on publicly available data revealed superior cost-effectiveness of FMT in IBD patients with rCDI, relative to antibiotic treatment ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effective analysis from the payer's perspective is crucial for health authorities to create a reimbursement policy for FMT in rCDI. Despite the limited number of cases, variations in antibiotic and FMT costs, and the heterogeneous study designs of published FMT-related economic evaluation studies across different countries, the latest systematic review published in 2020 concludes that FMT appears to be a cost-effective treatment for rCDI ( 31 ). However, only one study from Hong Kong based on publicly available data revealed superior cost-effectiveness of FMT in IBD patients with rCDI, relative to antibiotic treatment ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Randomized, controlled trials, systematic reviews, and meta-analyses suggest that patients with recurrent or refractory CDI in whom medical treatment has failed should be considered for fecal transplantation. 209,[213][214][215][216][217][218][219] In general, conventional antibiotic treatment should be used for at least 2 recurrences (ie, 3 CDI episodes) before offering fecal microbiota transplantation. 18 In terms of the technical aspects involved, randomized, controlled trials have shown similar CDI cure rates after fecal transplants performed with fresh and frozen fecal samples.…”
Section: Recurrent and Refractory CDImentioning
confidence: 99%
“…Given the growing interest in the use of FMT for rCDI treatment [ 17 ], it becomes important to support healthcare decision-making regarding the implementation of FMT in clinical practice. Previous systematic reviews have evaluated the cost-effectiveness of providing FMT for both index CDI and rCDI and have highlighted several concerns about the methodological quality of existing health economic evaluations [ 18 , 19 ]. However, the impact of these concerns on the conclusions of the studies has yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%